A d-pinitol transporter, LjPLT11, regulates plant growth and nodule development in Lotus japonicus. (30th August 2021) - Tian, Lu; Liu, Leru; Xu, Shaoming; Deng, Rufang; Wu, Pingzhi; Jiang, Huawu; Wu, Guojiang; Chen, Yaping
Abstract : LjPLT11 is localized to peribacteroid membranes, responsible for intracellular d -pinitol transport in infected nodule cells, negatively affects plant growth, and is required for nodule development in Lotus japonicus . Abstract: Polyol transporters have been functionally characterized in yeast and Xenopus laevis oocytes as H + -symporters with broad substrate specificity, but little is known about their physiological roles in planta . To extend this knowledge, we investigated the role of LjPLT11 in Lotus japonicus–Mesorhizobium symbiosis. Functional analyses of LjPLT11 in yeast characterized it as an energy-independent transporter of xylitol, two O -methyl inositols, xylose, and galactose. We showed that LjPLT11 is located on peribacteroid membranes and functions as a facilitative transporter of d -pinitol within infected cells of L. japonicus nodules. Knock-down of LjPLT11 ( LjPLT11i ) in L. japonicus accelerated plant growth under nitrogen sufficiency, but resulted in abnormal bacteroids with corresponding reductions in nitrogenase activity in nodules and plant growth in the nitrogen-fixing symbiosis. LjPLT11i nodules had higher osmotic pressure in cytosol, and lower osmotic pressure in bacteroids, than wild-type nodules both 3 and 4 weeks after inoculation of Mesorhizobium loti . Levels and distributions of reactive oxygen species were also perturbed in infected cells of 4-week-old nodules in LjPLT11i plants. The results indicate that LjPLT11 plays a key role in adjustment of the levels of its substrate pinitol, and thus maintenance of osmotic balance in infected cells and peribacteroid membrane stability during nodule development.